The Diplomacy of Islamic Powers in the Malacca Strait - Saeri, Mohammad; Purwasandi, Purwasandi; Wahyudi, Herry; Hidayatullah, Nur Luthfi (The Sunan Ampel Review of Political and Social Sciences, 2025)
The Strait of Malacca has been a strategic route for the meeting of economic, cultural, ideological and political interests since thousands of years ago. One of the impacts of this strategic meeting was the emergence of Islamic powers in the form of large Islamic kingdoms in the early 9th century. The existence of the Islamic powers of the Malacca Strait was revealed through a search of both primary and secondary documents. The results of this study prove that the emergence of Islamic powers in the Malacca Strait occurred through economic and cultural diplomacy, making it easier to strengthen the influence of Islamic ideology among the people along the Malacca Strait, both in Sumatra and Peninsular Malaysia. This strong and widespread influence of the Islamic religion became the basis for the establishment of large kingdoms which formed governments based on Islamic political principles. The clash of economic, cultural, ideological and political interests continued between the Islamic forces of the Malacca Strait and the Western powers as new arrivals which ended with the collapse of the Islamic forces of the Malacca Strait.